Graduate Curricula in Software Engineering and Software Assurance: Need and Recommendations - Hilburn, T. B.; Kornecki, A. J. (Elektronika ir Elektrotechnika, 2010)
The paper describes the results of two graduate curriculum projects: GSwE2009, which developed Graduate Software Engineering 2009: Curriculum Guidelines for Graduate Degree Programs in Software Engineering and MSwA2010, a current project, which is developing a Master of Software Assurance Reference Curriculum. The authors, who actively participated in the development of the recommendations, discuss the background, identification of the programs objectives and outcomes, relation to the respective Bodies of Knowledge, the audience and the required preparation, proposed curricula architecture, and the implementation comments.